2021
DOI: 10.3390/plants10071438
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antidiabetic Potential of Extracts of Urtica dioica, Apium graveolens, and Zingiber officinale in Mice, Zebrafish, and Pancreatic β-Cell

Abstract: Medicinal plants are commonly used in the treatment of diabetes, particularly as they contain flavonoids and phenolic compounds. The present study aims to investigate the activities of a polyherbal formulation made from Urtica dioica, Apium graveolens, and Zingiber officinale (UAZ) against streptozotocin–nicotinamide ((STZ-NA)-induced type 2 diabetes in CD1 mice, glucose-induced type 2 diabetes (T2DM) in zebrafish, and high glucose-induced damage in RINm5F pancreatic β-cells. In fasting mice, plasma glucose, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…This could be because the antioxidant defense system was improved [47]. Similar findings were made by Pérez Gutiérrez et al (2021), who showed that the Urtica dioica extract boosted the antioxidant enzymatic activity of SOD and CAT, which increased the levels of GSH while lowering the MDA in hepatic tissues in mice [48]. U. dioica leaves have been shown to have a high concentration of antioxidant and free radical scavenger components, which can reduce the high level of oxidative stress found in malignant cells [49].…”
Section: Discussionsupporting
confidence: 74%
“…This could be because the antioxidant defense system was improved [47]. Similar findings were made by Pérez Gutiérrez et al (2021), who showed that the Urtica dioica extract boosted the antioxidant enzymatic activity of SOD and CAT, which increased the levels of GSH while lowering the MDA in hepatic tissues in mice [48]. U. dioica leaves have been shown to have a high concentration of antioxidant and free radical scavenger components, which can reduce the high level of oxidative stress found in malignant cells [49].…”
Section: Discussionsupporting
confidence: 74%
“…Several plant constituents (such as flavonoids) detected in D. barnimiana are known to decrease TGs, TC, LDL-C, and VLDL-C. 47,54 Absorption of free fatty acids and free cholesterol can be inhibited by intervening the enzymatic activity of pancreatic lipase and pancreatic cholesterol esterases, thereby preventing hyperlipidemia related to DM. The antihyperlipidemic effects of the extract could be attributed to inhibition of those enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the insulin level in albino rat serum was performed using the protocol of enzyme-linked immunosorbent assay. 21 …”
Section: Methodsmentioning
confidence: 99%